2021
DOI: 10.1080/23766808.2021.1878982
|View full text |Cite
|
Sign up to set email alerts
|

On the occurrence of a highly localized outbreak of a saturniid in lowland east Ecuador: a case study and literature review

Abstract: For decades, outbreaks of insect herbivores in tropical forests were considered unusual or rare events primarily because of high plant diversity and the top-down impact of enemies. An alternative explanation is that these outbreaks are common but occur on sparsely distributed hosts high in the canopy and at scales of one or a few individual trees. Here, we report an outbreak of a saturniid in the genus Citioica Travassos & Noronha near the Amazon Basin of Ecuador on a single tree of Inga edulis Mart. The outbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Insect outbreaks likely occur more frequently and with greater impact where host trees are dominant or distributed in large, dense stands (Carson & Root, 2000). Many examples support this idea, but outbreaks can also defoliate small, scattered populations and individual trees (Nair, 2007; Sutton et al, 2021). According to the resource concentration hypothesis, we predicted that the outbreak would occur earlier and result in higher herbivore densities in the koa‐dominated reforestation stands due to rapid discovery by moths and superabundant food for caterpillars (Carson & Root, 2000; Root, 1973), and we found that the age structure of caterpillars was initially more advanced at the reforestation sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insect outbreaks likely occur more frequently and with greater impact where host trees are dominant or distributed in large, dense stands (Carson & Root, 2000). Many examples support this idea, but outbreaks can also defoliate small, scattered populations and individual trees (Nair, 2007; Sutton et al, 2021). According to the resource concentration hypothesis, we predicted that the outbreak would occur earlier and result in higher herbivore densities in the koa‐dominated reforestation stands due to rapid discovery by moths and superabundant food for caterpillars (Carson & Root, 2000; Root, 1973), and we found that the age structure of caterpillars was initially more advanced at the reforestation sites.…”
Section: Discussionmentioning
confidence: 99%
“…In tropical forests where host plant diversity is high and species distributions are scattered, insect outbreaks tend to occur at small spatial scales, sometimes involving only single host plants (Dyer et al, 2012; Janzen, 1981; Sutton et al, 2021). The ecological consequences of such outbreaks are likely to have limited, local impacts even though the vigor and reproduction of individual trees and their associated plant and animal communities might be affected.…”
Section: Introductionmentioning
confidence: 99%